Early Ideas of Reform in Hamka’s Ayahku: A Historical and Religious Struggle of Muhammadiyah in Minangkabau - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (Journal of Indonesian Islamic Studies, 2025)
The paper aims to study the historical background of Islamic reform movement in West Sumatera with particular reference to the idea of Haji Abdul Malik Karim Amrullah or his pseudonym Hamka (1908-1981). The main issues discusses is the context of socio-religious reform brought forth by Hamka in the quest of modernity and its enriching narrative of renewal and enlightening spiritual cause. Toward this end, this research aims to highlight Hamka’s significant work and aspiration for reform and the influence it developed in furthering his cause and legacy and monumental contribution in the history and tradition of reform in the Malay world. The study is based on normative and qualitative approaches in the form of content analysis. The data was conceptually analysed using descriptive, comparative and integrative method. The study found that Hamka’s modern idealism was instrumental in driving new consciousness of Islamic movement for reform (islah) and renewal (tajdid) in the Malay world contributing to unprecedented religious struggle that erupted in the late 20th century in Malay Archipelago. It reflected the force of modern ideas espoused by the leading Egyptian-mufti and polymath Shaykh Muhammad Abduh (1849-1905) that had brought decisive and greatest influence in the region. The implication of study is the creation of significance framework of religious ideal embedded in the practice of Islamic modernity adopted from Hamka’s enlightening works and insights that present higher Islamic religious ideal and principle and the dynamic aspiration Kaum Muda (the young faction) in the context of its socio-religious development and influence reflecting their modern philosophy and construct.